Intimate Partner Violence Prevention and Intervention Group-Format Programs for Immigrant Latinas: a Systematic Review - Marrs Fuchsel, Catherine L. (Journal of family violence, 2021)
Immigrant Latinas (IL) experiencing intimate partner violence (IPV) often experience barriers to accessing formal support systems due to immigration-related issues (e.g., fear of deportation, language proficiency, lack of family support in the U.S.). This paper contains a systematic review of peer-reviewed published articles within the past 25 years addressing IPV prevention and intervention programming designed for this vulnerable population. We examined specific group-format programs and curricula conducted at community-based agencies with social services across the country. Qualitative analysis of the 10 articles that met search criteria (i.e., programs must be culturally specific, designed to serve IL, conducted in group-format, focused on IPV intervention or prevention) generated information regarding the nature of group interventions addressing this issue and population. Several themes emerged upon completion of the qualitative review describing key characteristics of each intervention. All reviewed articles reported generally positive outcomes using a variety of methods. Studies using quantitative methods found statistically significant outcomes for constructs including depression, self-esteem, and knowledge of wellness. Professionals from diverse practice settings working with IL would likely benefit by developing intervention and prevention group-format programming to address this problem.